The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s41936-020-00175-x
|View full text |Cite
|
Sign up to set email alerts
|

Harderian gland of flying and non-flying birds: morphological, histological, and histochemical studies

Abstract: Background: The aim of the present study is to describe the morphological and histological features of Harderian gland (HG) in long-legged wadding bird (ibis) and different domestic birds (duck, goose, and pigeon). The HG of forty adult male and female from the four avian species constituted the material of the study. Result: The HG extended from the optic nerve to the rostral part of the eyeball presents two extremities, one posterior and other anterior, from which the excretory duct was arisen. Between two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
(36 reference statements)
0
14
0
3
Order By: Relevance
“…Unlike rabbits, other mammals and birds contain acidic mucosubstances in the tubular alveoli of the gland (36,37,38). This indicates significant species-specific features in the Harderian gland's functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike rabbits, other mammals and birds contain acidic mucosubstances in the tubular alveoli of the gland (36,37,38). This indicates significant species-specific features in the Harderian gland's functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies (i.e. Beheiry et al, 2020; Dubey et al, 2014; van Ginkel et al, 2009; Shawki et al, 2019) have reported that the head‐associated lymphatic tissue system in bird includes the Harderian gland, based on the presence of interstitial lymphatic tissue (plasma cells). Additionally, Klećkowska‐Nawrot et al (2015) reported that the lacrimal gland is not responsible for immunoglobulin production.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies (i.e. Beheiry et al, 2020;Dubey et al, 2014;van Ginkel et al, 2009;Shawki et al, 2019) have reported that the head-associated lymphatic tissue system in bird includes the Harderian gland, based on the presence of interstitial lymphatic tissue (plasma cells).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic examination of the Harderian gland demonstrated that it is a multilobular gland, with each lobe constructed of secretory acini (Beheiry et al, 2020). The superficial cells of the glandular body produce serous secretion, and the deep cells produce mucous secretion (Mobini, 2012).…”
Section: Introductionmentioning
confidence: 99%